2015
DOI: 10.4103/0366-6999.158371
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein –717A>G and –286C>T>A Gene Polymorphism and Ischemic Stroke

Abstract: Background:Inflammation plays a pivotal role in the formation and progression of ischemic stroke. Recently, more and more epidemiological studies have focused on the association between C-reactive protein (CRP) −717A > G and −286C > T > A genetic polymorphisms and ischemic stroke. However, the findings of these researches are not conclusive.Methods:We performed a meta-analysis to determine whether these two polymorphisms are associated with the risk of ischemic stroke. Eligible studies were identified from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…(2016), Liu et al. (2015), and Chen et al. (2014), respectively, reported the connection between CRP gene polymorphisms and IS susceptibility.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…(2016), Liu et al. (2015), and Chen et al. (2014), respectively, reported the connection between CRP gene polymorphisms and IS susceptibility.…”
Section: Discussionmentioning
confidence: 96%
“…in CRP genes and IS (González-Giraldo et al, 2016), one showed scant evidence to support a role for CRP gene rs2794521 polymorphisms in ischemic stroke predisposition, (Liu et al, 2015) and one could provide the first proof that genetic variants (rs1130864 and rs2794521) within the CRP locus are associated with ischemic stroke. (Chen et al, 2014) According to the best of our knowledge, this is the first thorough meta-analysis and systematic review analyzing the association of five SNPs in the CRP gene with IS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic brain injury is characterized by inflammation. However, data regarding a polymorphism in the CRP gene, which has been reported in candidate gene analysis as an independent risk factor for stroke, have been conflicting [122, 123]. Other components of the inflammatory cascade studied include IL-1a, TNFα, IL-10, ICAM-1, though evidence has again been inconsistent [124128] with studies limited by heterogeneity and small sample size.…”
Section: Af Genetics and Strokementioning
confidence: 99%
“…The volatile components of AMR play an important role to generate Siqi and Wuwei. Previous investigations have demonstrated that the volatile components of AMR have the effects of anti-inflammation [4], antiulcer [5], prevention of hypoglycemia [6], anti-oxidation [7], immunomodulation [8], antitumor cells [9], anti-aging, and hepatic protection [10,11]. Both crude AMR and its processed products (stir-frying with wheat bran) are frequently used clinically, and the appropriate processing methods can significantly alter the pharmacological properties of the original Chinese medicinal herbs, that is, the reduction of drug toxicity and the enhancement of pharmaceutical efficacy [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%